2021
DOI: 10.1111/jocn.15548
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between emotional intelligence and negative emotions of front‐line nurses during the COVID‐19 epidemic: A cross‐sectional study

Abstract: Aims and Objectives The purpose of this study was to understand the emotional intelligence level (EI) and negative emotional status of the front‐line nurses in the epidemic situation and to further explore the relationship between them. Background During the COVID‐19 epidemic, under the influence of multiple factors, nurses were vulnerable to negative emotions. While previous studies have explored, the role of emotional intelligence in negative emotions, the relationship between the two has not been sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 33 publications
7
51
2
4
Order By: Relevance
“…The anxiety score was 8.70 points, indicating mild anxiety, and the stress score was 10.84 points, indicating a normal level of stress. This is similar to the results of previous studies in other countries, reporting a normal level of depression, mild anxiety, and a normal level of stress during the current COVID-19 pandemic [ 10 , 11 ]. Thus, it can be interpreted that similar levels of depression, anxiety, and stress have been experienced by nurses globally during this pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The anxiety score was 8.70 points, indicating mild anxiety, and the stress score was 10.84 points, indicating a normal level of stress. This is similar to the results of previous studies in other countries, reporting a normal level of depression, mild anxiety, and a normal level of stress during the current COVID-19 pandemic [ 10 , 11 ]. Thus, it can be interpreted that similar levels of depression, anxiety, and stress have been experienced by nurses globally during this pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…This abovementioned result is inconsistent with Sun et al’s [ 10 ], who reported that being a charge nurse was not a factor affecting stress during the COVID-19 pandemic, and that the level of stress was higher among head nurses. When considering the division of duties in the hospital, charge nurses are responsible for both administrative work and direct nursing care, while head nurses mainly perform administrative work [ 21 ].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Therefore, training and prevention programs should be developed that, among other consequences, reduce anxiety in the face of death. Among them, those focused on improving emotional intelligence could be of great value since they have proven helpful in different contexts [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also emailed the authors of 43 articles that missed critical information and were able to get the information to include 10 additional studies. Altogether, the process generated 131 articles for this meta-analysis (An et al, 2020; Ben-Ezra et al; Cai et al; Cao et al, 2020; Chen et al; Chen et al; Chen et al; Chen et al; Chen et al, 2020; Cheng et al; Choi et al; Dai, 2020; Dong et al, 2020; Du et al, 2020; Elhai et al, 2020; Fang et al, 2020; Feng et al, 2020; Fong et al, 2020; Fu et al, 2020; Gao, 2020; Guo et al, 2020; Guo, 2020; Han et al, 2020; Hong et al, 2020; Hou et al, 2020; Hu et al, 2020a; Hu et al, 2020b; Huang et al, 2020a; Huang et al, 2020c; Huang et al, 2020d; Jin et al, 2020; Juan et al, 2020; Lai et al, 2020; Lam et al, 2020; Lei et al, 2020; Leng et al, 2020; Li; Li et al, 2020a; Li et al, 2020b; Li et al, 2020c; Li, 2020a; Li et al, 2020d; Li et al, 2020e; Li, 2020b; Li et al, 2020f; Li et al, 2020g; Liang et al, 2020; Lin et al, 2020a; Lin et al, 2020b; Liu, 2020; Liu, in press; Liu et al, 2020a; Liu et al, 2020b; Liu et al, 2020c; Liu et al, 2020d; Liu et al, 2020e; Liu et al, 2020f; Lu et al, 2020a; Lu et al, 2020b; Lu et al, 2020c; Mi et al, 2020; Ni et al, 2020a; Ni et al, 2020b; Ning et al, 2020; Pan et al, 2020a; Pan et al, 2020b; Qi, 2020; Qian et al, 2020; Qian, 2020; Qiu et al, 2020; Que et al, 2020; Ren et al, 2020b; Shi et al, 2020; Si et al, 2020; Song et al, 2020; Song, 2020; Su et al, 2020; Sun et al, 2020a; Sun, 2020; Sun et al, 2020b; Sun et al, 2020c; Tan et al, 2020; Teng et al, 2020; Tu et al, 2020; Wang et al, 2020a;…”
Section: Resultsmentioning
confidence: 99%